Exploration and exploitation in early stage ventures and SMEs - Stettner, Uriel; Aharonson, Barak S.; Amburgey, Terry L. (Emerald, 2014)
This volume of Technology, innovation, entrepreneurship and competitive strategy is devoted to research aimed at understanding the implications of Exploration and Exploitation activities in early-stage ventures and small-and-medium enterprises (SMEs).
Keywords: Business & Economics -- Entrepreneurship.; Business strategy.; New business enterprises.; elektronické knihy; electronic books